THE EFFECT OF KNOW-WANT-LEARNED (KWL) STRATEGY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP TRI BHAKTI PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXT - Buqhariah, Imanul; Purwanti, Indah Tri; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The research was aimed to determine the effect of the Know-Want-Learned (KWL) strategy on the ability of the second year students of SMP Tri Bhakti Pekanbaru in comprehending descriptive texts. This pre-experimental research used the design of one group pretest-posttest and was carried out at Tri Bhakti School in Pekanbaru. A total of 27 students from class VIII.1 in the 2019/2020 academic year were selected as samples, they were selected by using the cluster random sampling. The Sample class was treated using the KWL strategy. The instrument used was a multiple-choice that consisted of 40 questions. Then, the data obtained from the pre-test and post-test were analyzed by SPSS version 23.0. The results show that the value of the pre-test is 46 and increased in the post-test to 77. Then the T-test was tested and obtained T-test > T-table (13,659 > 2,056) with a significant level of 5% which means there is a significant effect of the KWL strategy on the ability of the second year students of SMP Tri Bhakti Pekanbaru in comprehending descriptive texts.Key Words: Reading, Reading Comprehension, Descriptive Text, KWL Strategy